(-7-1x)(5-1x)=0

Simple and best practice solution for (-7-1x)(5-1x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-7-1x)(5-1x)=0 equation:


Simplifying
(-7 + -1x)(5 + -1x) = 0

Multiply (-7 + -1x) * (5 + -1x)
(-7(5 + -1x) + -1x * (5 + -1x)) = 0
((5 * -7 + -1x * -7) + -1x * (5 + -1x)) = 0
((-35 + 7x) + -1x * (5 + -1x)) = 0
(-35 + 7x + (5 * -1x + -1x * -1x)) = 0
(-35 + 7x + (-5x + 1x2)) = 0

Combine like terms: 7x + -5x = 2x
(-35 + 2x + 1x2) = 0

Solving
-35 + 2x + 1x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-7 + -1x)(5 + -1x) = 0

Subproblem 1

Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7

Subproblem 2

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Solution

x = {-7, 5}

See similar equations:

| 1-3x=22 | | 8=z/4=23 | | -36=-2A-9B+C | | -11-18-4w/5 | | 7(7+25)+(5+6)10= | | 2x-1+5+x=180 | | 8-1/7u5 | | 20+2y-5=9y-13-3y | | 26=4A+2B | | 3(4+25)-12+-15= | | -6x+20=4x-30 | | 18x+12y=165 | | (2a^-5b^4c^3)^-2/(3a^3b^-7c^3)^2 | | A^2-3a-45=0 | | A^2-3a-34=0 | | 3/8v3 | | x^2+4x-10= | | 10(x+3)=31 | | 111-4u/3 | | 180*(n-2)=1 | | 6sin^2x+9sinx+3=0 | | 5d=3m-14 | | -2v/7-10-15 | | y=7x+55 | | 3(y+-2)+-1=1 | | 6(y-1)=3y-15 | | 2*x+x^2+y^2+17=12*y | | 2x^2-10d-9=0 | | -6p=3(2p-3)-4(-10+4p) | | 3y+-6+-1=1 | | 138-1/7y | | 6x^3+28x^2+16x= |

Equations solver categories